2016
DOI: 10.3390/en9090701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sintering Temperature and Applied Load on Anode-Supported Electrodes for SOFC Application

Abstract: Anode-supported cells are prepared by a sequence of hot pressing and co-sintering processes for solid oxide fuel cell (SOFC) applications. Commercially available porous anode tape (NiO/YSZ = 50 wt %/50 wt %), anode tape (NiO/YSZ = 30 wt %/70 wt %), and YSZ are used as the anode substrate, anode functional layer, and electrolyte layer, respectively. After hot pressing, the stacked layers are then sintered at different temperatures (1250 •

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A porous microstructure that showed partial sintering was achieved, which was consistent with the measured densities of the samples. Utilization of the cold sintering process resulted in limited grain growth in the anode which enhanced long triple-phase boundary densities when compared to conventionally sintered NiO-8YSZ anodes in the literature. , For example, Brown et al reported that Ni-8YSZ anodes fabricated by cosintering of NiO and 8YSZ powders contained particles that were up to 3 μm in size when the sintering procedure was carried out at 1300 °C . Particle sizes up to 5 μm were observed when the sintering temperature was raised to 1500 °C .…”
Section: Resultsmentioning
confidence: 99%
“…A porous microstructure that showed partial sintering was achieved, which was consistent with the measured densities of the samples. Utilization of the cold sintering process resulted in limited grain growth in the anode which enhanced long triple-phase boundary densities when compared to conventionally sintered NiO-8YSZ anodes in the literature. , For example, Brown et al reported that Ni-8YSZ anodes fabricated by cosintering of NiO and 8YSZ powders contained particles that were up to 3 μm in size when the sintering procedure was carried out at 1300 °C . Particle sizes up to 5 μm were observed when the sintering temperature was raised to 1500 °C .…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to find that there are very similar iop-Vop relationships between cells 1 and 2, while estimated iop based on the relevant smaller electrode surface area (i.e., Aca in current case). There is no obvious difference between the performance results For a button cell, the support component layer is always fabricated with a relative lager surface area compared with the measured electrode [32] (i.e., the anode surface area in current button cell is 3.14 cm 2 and the corresponding surface area of measured cathode is only 2 cm 2 ). Obviously, for a specified output voltage V op , the responded operating current density i op can be evaluated by two ways, divided the output current I op by A an for a larger value or A ca for a lower value.…”
Section: Resultsmentioning
confidence: 99%
“…The cell includes three anode layers, each with a thickness of 180 µm, an anode functional layer with a thickness of 20 µm, an electrolyte layer with a thickness of 18 µm, and a cathode paste layer with a thickness of 25 µm. The four kinds of layers were stacked (cathode layer at the top, then the electrolyte layer, then the anode functional layer, and the anode layers at the bottom) [23]. The SOFC cells fabrication procedure is shown schematically in Figure 1.…”
Section: Anode-supported Cell Fabricationmentioning
confidence: 99%